(untitled) (Archaeologia Adriatica, 2022)
The paper analyses finds of devotional (religious) medals recovered in the excavation in the interior of the church of St Dominic that was conducted by the Department of Archaeology of the University of Zadar. The excavation unearthed post-medieval walled tombs and burials without grave architecture. Among other finds, they contained 29 medals commemorating various saints, the ones featuring the depiction of Our Lady of Loreto being the most numerous. All medals date to the 17th and 18th centuries.